The simplification of Upstream Oil and Gas Business license in Indonesia (Research, Society and Development, 2020)
Oil and Gas is natural resources in Indonesia which is the business related to is regulated in Law Number 22 of 2001 about Oil and Gas. There are two kinds of business related to oil and gas that are upstream and downstream. In upstream oil and gas business, there still a lot problem faced by the government and the enterprises. Thus, it is needed simplification license for upstream oil and gas in order to increase investment which will lead into effective and efficient public services. Normative law here is applied as method to analyze the regulations related to oil and gas industry license. Furthermore, the approach used here are statute approach and conceptual approach. The results reveal that the Licensing for Utilization of Resources and/or Infrastructure of Upstream Oil and Gas Business does not yet have a synchronization of authority in the issuance of these licenses. In order to obtain effective and efficient upstream oil and gas business licensing services, it is necessary to synchronize and harmonize regulations and it is need a one-stop licensing service as referred to the Presidential Regulation Number 97 of 2014 concerning Implementation of One Stop Integrated Services.